THE INFLUENCE OF TAXATION KNOWLEDGE, TAX SOCIALIZATION AND TAX ADMINISTRATION ON TAXPAYER COMPLIANCE (EMPIRICAL STUDY IN MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) TOBAT VILLAGE, BALARAJA SUB-DISTRICT, TANGERANG REGENCY, BANTEN PROVINCE) - Mediawahyu Lestari, Steffi; Apollo Daito (Dinasti Publisher, 2020)
This study aims to obtain empirical evidence about the influence of taxation knowledge, tax socialization, and tax administration on taxpayer compliance. The research sample was 38 micro small and medium enterprises in the village of Tobat, Balaraja sub-district, Tangerang regency, Banten province, which made a business certificate. Data analysis uses path analysis. The PLS application is used to test hypotheses. The overall results of this study state that taxation knowledge does not affect taxpayer compliance. tax socialization and tax administration affect taxpayer compliance. This study has limitations including, the sample used is less than 100 samples, the data used are only primary data is expected to further research using a larger sample and supported by secondary data